Exercising Teacher Agency for Inclusion in Challenging Times: A Multiple Case Study in Chilean Schools - Herrera-Seda, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Teacher agency has been recognised as a relevant concept for understanding the role of teachers in the current uncertain and changing contexts. However, its study about inclusive education is recent, especially in the Global South. This study analysed how teachers exercised agency for inclusive education during the COVID-19 crisis and the conditions that enabled or inhibited agency. This article explores Chilean schools, where neoliberal policies particularly challenge teachers’ agency. A multiple case study was conducted based on mixed methods. Online questionnaires were carried out with 154 teachers from 5 schools. In addition, five teachers from each school participated in in-depth group interviews. The findings show how teachers promoted students’ learning and participation in response to the challenges of the pandemic. Teachers mobilised resources to adapt to the context of uncertainty and supported one another. Among the influential factors, education policy constraints and control were reduced during the pandemic, thus creating opportunities to achieve agency for inclusion across the schools. At the same time, leadership, collaboration, and vision influenced agency differently in each school. While not aiming for major transformations, this study shows how teachers develop initiatives to adapt their practices and contribute to building inclusive schools despite contextual constraints. © 2025 by the authors.